Long-term shifts in the spatial distribution of Common Cranes Grus grus - Morgane Gicquel; Lovisa Nilsson; Juan C. Alonso; Matthew Low; Javier A. Alonso; Dmitrijs Boiko; Damon Bridge; Patrick Dulau; Thomas Heinicke; Anne Kettner; Yosef Kiat; Petras Kurlavičius; et al. (Journal of Ornithology, 2026)
Migratory bird distributions are inherently dynamic and vary with seasons, but are also increasingly influenced by climate and land-use changes. Understanding these shifts is crucial for interpreting ecosystem dynamics and guiding future conservation efforts. In this study, we analysed 187,779 resightings (1985–2021) of 5,120 colour-banded Common Cranes ( Grus grus ), originating from 8 northern European countries, to examine long-term spatiotemporal distribution dynamics along the Western and Central European flyways. Our results show that the flyway use has remained largely consistent with the previous studies: most cranes follow the Western European flyway, wintering in France and Spain, whilst a smaller proportion follow the Central European flyway, wintering in Hungary and occasionally reaching Israel and North Africa. However, we also observed a pronounced northward shift in wintering distribution over the past 4 decades. At the same time, breeding distributions showed a slight southward expansion, potentially reflecting both population growth and changes in marking effort. Our results demonstrate the importance of long-term monitoring in detecting range shifts and highlight the need for adaptive conservation planning in the face of accelerating climate and land-use change.